1, 2 Napthaquinone-4-sulphonic acid sodium salt Chromogen for Quantifying the Thiazolidinedione Class of drug in Human Plasma Spiked drug sample, bulk and marketed formulation as per Quality ICH guidelines. (Cuestiones de Fisioterapia, 2025)
The current UV approach, which uses sodium salt 1, 2, napthaquinone-4-sulphonate, is comparatively easy to use, quick, and very sensitive for determining pioglitazone hydrochloride. The wavelength at which the pioglitazone hydrochloride exhibited absorption maxima was 455 nm. With a correlation value of 0.9996, the linearity range of pioglitazone hydrochloride was 5-120μg/ml. When pioglitazone hydrochloride was precisely measured, the result was determined to be less than 2. The outcomes of the suggested approach were deemed acceptable and suitable for estimating pioglitazone hydrochloride for regular quality control of the drug in the formulation and marketed formulation. A rapid and sensitive bio-analytical method was developed for the determination of Pioglitazone Hydrochloride in human plasma by protein precipitation extraction method. The ICH guidelines Q2R1 have been followed in the validation of this technique and M10 for bio-analytical method.